Benefits and risks of transgenic products: Awareness-building - Jalil Badam Firouz; Mona Izadian; Farhad Hosseini Tayefeh (محیط زیست و توسعه فرابخشی, 2020)
The Cartagena Protocol was adopted to achieve a common and coordinated solution for the transboundary movement of transgenic organisms, establish confidence and legitimacy in the field of biosafety regulations in the world, and increase global coordination. Under Clause 2 of Article 23 of the Protocol, States Parties are required to consult with the public and public institutions on the decision-making and policy-making of genetically modified species and to make the results of such consultations available to the public. In recent years, transgenic products have entered the diet of the Iranian people, but there has made no proper awareness about their benefits or harms for the people. Since the genetic structure of transgenic plants is altered through genetic engineering, and this change is usually done to improve the plant's resistance to certain pests or plant diseases, there is concern that these plants have also become resistant to drugs and cause abnormalities and the spread of diseases in humans. The Cartagena Protocol emphasizes the need for labeling, but despite the use of transgenic products in Iran, labeling and percentaging have not been done on all products and it is necessary to pay special attention to the implementation of the latest regulation of the Food and Drug Administration regarding transgenic events.